Health policy in a globalising world / edited by Kelley Lee, Kent Buse and Suzanne Fustukian. - Lee, Kelley, 1962-; Buse, Kent; Fustukian, Suzanne, 1953- (Cambridge University Press, 2002)
The contributors to this study argue that health policy formulation is being affected by globalization and that these effects are, in turn, contributing to the kind of global health issues being faced today.